Improved pitch control strategy for the robust operation of wind energy conversion system in the high wind speed condition - Chen, Ziyang; Shi, Tingna; Song, Peng; Li, Chen; Cao, Yanfei; Yan, Yan (International journal of electrical power & energy systems, 2023)
•A novel robust pitch controller to enhance the dynamic performance in WT output power/speed in the high wind speed domain.•The proposed controller is independent of the exact model parameters of WTs, easy to implement in practice.•Improving access to the rotor acceleration signal with minimizing system noise amplification.•Giving a rigorous stability demonstration for the closed-loop system.•Developing a refined HIL platform for wind energy conversion systems to validate the approach's effectiveness. The wind energy conversion system is a complex dynamic system with strong nonlinearity, perturbation, and uncertainty. In this paper, a novel optimal pitch control strategy is proposed to improve the ability to stabilize the captured wind energy, so as to realize robust operation in the high-wind-speed condition for wind turbines (WT) subject to unmodeled system disturbances and uncertainty. This control strategy combines three critical techniques: optimal pitch control law determination, disturbance compensation, and acceleration estimation. Among them, the optimal pitch control law is determined by utilizing the Hamilton-Jacobi-Bellman equation, regarding the minimization of the quadratic performance index. The total system uncertain disturbance is compensated by a designed extended state observer, making the pitch control approach almost independent of precise WT model parameters, markedly reinforcing the control system robustness. To prevent system noise amplification from direct differential means in acquiring rotor acceleration, we employ a fast-converging acceleration estimator to obtain the rotor acceleration feedback signal required by the pitch control law. System stability is proved using the Lyapunov theory. The comparative results on the developed hardware-in-the-loop test platform validate the effectiveness of the proposed solution, demonstrating that it provides superior dynamic performance in WT electrical power and speed with reduced fluctuation, overshoot, and regulation time while maintaining robustness against disturbances.